2018
DOI: 10.1002/aic.16467
|View full text |Cite
|
Sign up to set email alerts
|

Hunting ionic liquids with large electrochemical potential windows

Abstract: Ionic liquids (ILs) with large electrochemical potential windows (EPWs) are ideally suited to improve the energy and power density of electrical devices for energy storage. However, guidelines are scarcely available for the selection or systematic screening of ILs for practical applications. Here, we present theoretical predictions for the EPW of thousands of cation‐anion pairs based on a long‐range corrected hybrid density functional theory. The cathodic and anodic potential limits were estimated from the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 39 publications
2
77
0
1
Order By: Relevance
“…Recently, DFT calculation has been applied to predict the electrochemical potential windows for ionic liquids to accelerate the process for experimental selection. 358 Theoretical and experimental works have shown that unlike solvated electrolytes, the EDL structure of ionic liquids does not align with the classic EDL models (for details of the model see Section 2.1). 36,41,359 In ionic liquids, the existence of ion pairs and compact packing of ions result in a short-to long-range of electrostatic force based on the applied voltage.…”
Section: Advanced Electrolytesmentioning
confidence: 99%
“…Recently, DFT calculation has been applied to predict the electrochemical potential windows for ionic liquids to accelerate the process for experimental selection. 358 Theoretical and experimental works have shown that unlike solvated electrolytes, the EDL structure of ionic liquids does not align with the classic EDL models (for details of the model see Section 2.1). 36,41,359 In ionic liquids, the existence of ion pairs and compact packing of ions result in a short-to long-range of electrostatic force based on the applied voltage.…”
Section: Advanced Electrolytesmentioning
confidence: 99%
“…As mentioned above, a low dynamic viscosity is a prerequisite for electrolytes because it is paralleled by a high ion mobility, as evident from a high specific conductivity. Tetracyanoborate‐ILs ( TCB ‐ILs, Figure ) were the first cyanoborate‐ILs that were synthesized and applied for electrochemical devices, for example, DSSCs . Later, applications in batteries and supercapacitors were also studied .…”
Section: Borate Anions and Anionic Boron Clusters As Building Blocks mentioning
confidence: 99%
“…Wie bereits erwähnt, ist eine niedrige dynamische Viskosität eine Grundvoraussetzung für eine erfolgreiche Anwendung als Elektrolyt, da diese mit einer hohen Ionenmobilität und damit verbunden mit einer hohen spezifischen Leitfähigkeit einhergeht. Tetracyanoborat‐ILs ( TCB ‐ILs, Abbildung ) waren die ersten Cyanoborat‐Ils, die dargestellt und erfolgreich in elektrochemischen Vorrichtungen wie DSSCs eingesetzt werden konnten. In der Folge wurde das Anwendungsspektrum von TCB ‐ILs auf Batterien und Superkondensatoren ausgeweitet und in den letzten Jahren konnten zahlreiche weitere Cyanoboratanionen und deren ILs realisiert und im Detail untersucht werden.…”
Section: Boratanionen Und Anionische Borcluster Als Bausteine Für Eneunclassified